Mister Rogers' neighborhood. A day at the circus [videorecording (DVD)] - Rogers, Fred; Aberlin, Betty (Anchor Bay Entertainment, 2005)
"Circus fun": See performances by trapeze artists, acrobats, elephants and more! Go behind the scenes with Mister Rogers and learn how clowns put on their make-up and talk with some of the many other people who work at the circus. "Music adventure": Mister Rogers visits a friend who has a fascinating collection of musical instruments from around the world.